Liar's point [large type] - Griffin, Laura, 1973- (Griffin, Laura, 1973- Texas murder files, 2025)
"Can she find the truth in a growing web of lies? Detective Nicole Lawson is fed up with her job and non-existent love life, especially when her first date in months gets cut short before it even starts by an urgent call from the chief of police. A body has been discovered at Lighthouse Point, and news of the homicide quickly reverberates through Nicole's hometown. Leading the investigation is Emmet Davis, a veteran detective and Nicole's fiercest rival at work. With Emmet calling the shots, Nicole is keen to find a lead, but when another body appears and she starts to see a bizarre pattern, no one believes her. As the stakes grow ever higher, Nicole must put aside her tumultuous feelings and work closely with Emmet to figure out who is targeting her beloved hometown . . . before she becomes a target herself."--